Pituitary Adenoma Coexistent with Sellar Clear Cell Meningioma Unattached to the Dura: Case Report and Treatment Considerations - Chatain, Grégoire P.; Chee, Keanu; Driscoll, Meghan; Kleinschmidt-DeMasters, B.K.; Lillehei, Kevin O. (Journal of Neurological Surgery Reports, 2024)
Collision tumors involving the sella are rare. Intrasellar collision tumors are most commonly composed of a combination of pituitary adenomas and pituitary neuroendocrine tumors; however, collision tumors consisting of a pituitary adenoma and intrasellar meningioma are exceedingly rare. The authors present the case of a 47-year-old man who presented with progressive right eye vision loss. Magnetic resonance imaging showed a large, heterogeneously enhancing sellar mass with suprasellar extension. Using a transcranial approach with a right subfrontal craniotomy, near-total resection of the mass was achieved. Histologic analysis confirmed a diagnosis of a gonadotroph adenoma with concomitant clear cell meningioma (CCM). This patient was discharged with improvement in visual acuity and no signs of diabetes insipidus. Given the indistinguishable radiographic characteristics of pituitary adenoma and CCM, a preoperative diagnosis of a collision tumor was difficult. This case was uniquely challenging since the CCM component lacked the classic dural attachment that is associated with meningiomas on neuroimaging. CCMs are classified as central nervous system (CNS) World Health Organization (WHO) grade 2 tumors and tend to behave more aggressively, therefore warranting close surveillance for signs of tumor recurrence. This is the first case to report a collision tumor consisting of pituitary adenoma and CCM.
Keywords: collision tumors; meningioma; pituitary adenoma; sella